Accelerated Entry Point Search Algorithm for Real Time Ray Tracing - COLLINS, STEVEN; MANZKE, MICHAEL; FOWLER, COLIN (My University, 2009)
Traversing an acceleration data structure, such as the Bounding Volume Hierarchy or kD-tree, takes a significant amount of the total time to render a frame in real-time ray tracing. We present a two phase algorithm based upon MLRTA for finding deep entry points in these tree acceleration data structures in order to speed up traversal. We compare this algorithm to a base MLRTA implementation. Our results indicate an across-the-board decrease in time to find the entry point and an increase in entry point depth. The overall performance of our real-time ray-tracing system shows an increase in frames per second of up to 36% over packet-tracing and 18% over MLRTA. The improvement is algorithmic and is therefore applicable to all architectures and implementations.
Spring Conference on Computer Graphics
PUBLISHED
Slovakia
Keywords: real-time ray-tracing; MLRTA; BVH; kD-tree; traversal algorithm